Métodos de densidade em otimização de topologia aplicados a subsistemas de edifícios - Pinho, Flávio Augusto Xavier Carneiro (2015)
Optimization techniques have been widely used in different engineering applications. In the case of structural conception, these techniques can be applied from the architectural concept, determining, for example, bracing structures to setting the best topology for concrete structures, as those compared to strut and tie models. In this context, this thesis presents techniques applied to topology optimization in subsystems of buildings. It is also presented a new software tool, modelled in object-oriented programming, seeking the solution for topology optimization problems assembling various technical problems unified in a single approach. The software tool was used to determine the best shape to bracing frames on a building submited to different loading combinations as well to compare the strut and tie models to foundation blocks. Results were compared to literature review, validating the unified computational procedure. Strut and tie models found in literature were compared to piled foundation blocks varying the number of piles, and whose geometry for larger number of piles are still not clearly defined.